Making healthcare decisions for terminally ill adults and elderly in rural Bangladesh: an application of social autopsy - Nurul Alam; Hafizur Rahman Chowdhury; Sayed Saidul Alam; Taslim Ali; Peter Kim Streatfield; Ian Douglas Riley; Alan D Lopez (Journal of Global Health Reports)
# Background